1996
DOI: 10.1111/j.1467-8624.1996.tb01918.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Occupational Aspirations and Expectations among Inner-City Boys

Abstract: The occupational aspirations and expectations of two populations of boys in grades 2, 4, 6, and 8 were examined in order (1) to describe what is unique about the development of job preferences among urban ghetto children who live in settings where many adult males are not well attached to the labor force and (2) to examine 6 reasons for any age- and population-dependent patterns there might be in job aspirations and job expectations. Findings show that boys tend to be more realistic about occupational aspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 10 publications
4
80
2
Order By: Relevance
“…However, another study showed that inner-city boys report aspiring to (and expecting) fewer white-collar or prestigious occupations than those from more affluent suburban areas (Cook et al, 1996). This suggests that adolescents of a low SES may aspire to improvement but their aspirations are relatively not as high as their more advantaged peers.…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 90%
See 1 more Smart Citation
“…However, another study showed that inner-city boys report aspiring to (and expecting) fewer white-collar or prestigious occupations than those from more affluent suburban areas (Cook et al, 1996). This suggests that adolescents of a low SES may aspire to improvement but their aspirations are relatively not as high as their more advantaged peers.…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 90%
“…However, goal pursuit may be thwarted by beliefs of low ability, control and environmental responsiveness. One of the difficulties of research in this area is that SES is often confounded by the ethnic composition of the sample (e.g., Cook et al, 1996). In future research it would be interesting to determine the unique contribution of each of these two influential factors to goal endorsement and goal pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…However, the little research that is available suggests that involvement of fathers in the lives of at-risk children is associated with better educational and behavioral child outcomes (Cook, Church, Ajanaku, Shadish, Kim, & Cohen, 1996;Furstenberg & Harris, 1993).…”
Section: Parent Promotion Of Child Developmentmentioning
confidence: 98%
“…Low-income students whose end goal is college matriculation may fall into an "expectations gap," where aspirations fail to align with access capability. Student expectations are more determinant than aspirations in leading to matriculation goals (Elliot, 2009;Cook et. al., 1996;Reynolds & Pemberton, 2001), indicating the importance of cultural capital as reflected in early expectations, regardless of assets.…”
Section: Assets Expectations and College Attainmentmentioning
confidence: 99%